Model Assessment of, for dan as Learning Terpadu dalam Mata Kuliah Reading Bahasa Inggris - Agung Prihantoro (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2022)
The research aim develops an integrated model of assessment of learning (AoL), assessment for learning (AfL) and assessment as learning (AaL) in English language reading subject of private Islamic universities in the Yogyakarta special province. The research methodology is Borg and Gall’s research and development (R & D). The respondents are students of the Sekolah Tinggi Agama Islam Masjid Syuhada (STAIMS) Yogyakarta dan of the Islam Faculty of the Yogyakarta Cokroaminoto University. The results are that the model increases learning outcomes of the English language reading subject in STAIMS Yogyakarta in 2019 dan in the Islam Faculty of the Yogyakarta Cokroaminoto University in 2021, but decreases them in the Islam Faculty of the Yogyakarta Cokroaminoto University in 2019. The model needs to revise again and test for more respondents of more than two private Islam universities with being based on right learning theories. However, the model can be applied to maximize the achievement of learning outcome of the English reading subject.